Lactobacillus reuteri DSM 17938 shortens acute infectious diarrhea in a pediatric outpatient setting - Ener Cagri Dinleyici; Nazan Dalgic; Sirin Guven; Ozge Metin; Olcay Yasa; Zafer Kurugol; Ozden Turel; Gonul Tanir; Ahmet Sami Yazar; Vefik Arica; Mesut Sancar; Adem Karbuz; et al. (Brazilian Society of Pediatrics, 2015)
Objective: Two randomized controlled clinical trials have shown that Lactobacillus (L) reuteri DSM 17938 reduces the duration of diarrhea in children hospitalized due to acute infectious diarrhea. This was the first trial evaluating the efficacy of L.reuteri DSM 17938 in outpatient children with acute infectious diarrhea. Methods: This was a multicenter, randomized, single‐blinded, case control clinical trial in children with acute watery diarrhea. A total of 64 children who presented at outpatient clinics were enrolled. The probiotic group received 1 × 108 CFU L. reuteri DSM 17938 for five days in addition to oral rehydration solution (ORS) and the second group was treated with ORS only. The primary endpoint was the duration of diarrhea (in hours). The secondary endpoint was the number of children with diarrhea at each day of the five days of intervention. Adverse events were also recorded. Results: The mean duration of diarrhea was significantly reduced in the L. reuteri group compared to the control group (approximately 15 hours, 60.4 ± 24.5 hours [95% CI: 51.0‐69.7 hours] vs. 74.3 ± 15.3 hours [95% CI: 68.7‐79.9 hours], p < 0.05). The percentage of children with diarrhea was lower in the L. reuteri group (13/29; 44.8%) after 48 hours than the control group (27/31; 87%; RR: 0.51; 95% CI: 0.34‐0.79, p < 0.01). From the 72nd hour of intervention onwards, there was no difference between the two groups in the percentage of children with diarrhea. No adverse effects related to L. reuteri were noted. Conclusion: L. reuteri DSM 17938 is effective, safe, and well‐tolerated in outpatient children with acute infectious diarrhea.